(untitled) (Research, Society and Development, 2020)
Introduction: Pregnancy corresponds to a period in which it should not be highlighted only by the development of a new being, but by a set of changes that can happen in the life of a pregnant woman, as is the case with aesthetic changes in her body and external modifications for receiving a child. Objective: To identify the main aesthetic changes during the gestational period. Methodology: Characterized as an integrative literature review through an exploratory, quantitative and qualitative approach, in which the Lilacs, Scielo Pubmed database was used to survey bibliographic data through the Virtual Health Library (VHL). Original articles in Portuguese and English published between 2009 and 2017, available online, in their entirety and as exclusion criteria, dissertations, systematic reviews, integrative, bibliographic or meta-analysis reviews were used as inclusion criteria for the research. As well as materials that did not have any association with the central theme of the research. Results and Discussion: Among the main changes observed during pregnancy, we can mention: breast enlargement, weight gain, development of stretch marks, varicose veins and melasma. Final Considerations: Several aesthetic changes can be investigated during pregnancy, but these negative impacts can be reduced with the apparatus of a health professional, so that pregnant women can obtain the necessary recommendations so that they can achieve a healthy pregnancy and development child.